Case report: Chylopericardium secondary to dialysis catheter related jugular venous thrombosis in two dogs receiving long-term hemodialysis - Woerde, Dennis J.; Palm, Carrie A.; Duler, Laetitia M.; Cowgill, Larry D.; Ames, Marisa K.; Culp, William T. N. (Frontiers in Veterinary Science, 2024)
Chylopericardium is a rare entity in veterinary medicine. In this report we document the development of chylopericardium in two dogs undergoing chronic hemodialysis. An 11-year-old female spayed Labrador retriever (Case 1) presented with acute coughing and lethargy 2 months following initial dialysis catheter placement and initiation of dialysis therapy for severe azotemia. Echocardiography demonstrated severe pericardial effusion and cardiac tamponade. Pericardial fluid analysis was consistent with chylous effusion. The dog underwent a subtotal pericardiectomy with thoracic duct ligation, and a PleuralPort™ was placed. The patient continued to receive outpatient hemodialysis therapy after pericardiectomy for several months until she died acutely at home. A 4-year-old male neutered Doberman (Case 2) was being treated for 2 months with outpatient hemodialysis for management of chronic kidney disease. On presentation for the 17 th hemodialysis treatment, the patient had increased respiratory rate. Echocardiography demonstrated pleural and pericardial effusions, and fluid analysis in both cavities was consistent with chylous effusion. Use of tissue plasminogen activator (TPA), clot removal and replacement of the catheter was attempted; however pleural and pericardial effusion continued. The patient was euthanized after 25 hemodialysis sessions as owners elected not to pursue more procedures. In both cases, the cause of the chylopericardium was suspected to be secondary to catheter-associated thrombosis and/or stenosis based on multiple imaging modalities. Despite use of rivaroxaban and clopidogrel concurrently in each case, the chylous effusion persisted. This case report describes clinical details of a rare complication of longterm indwelling dialysis catheters in two dogs.